2019
DOI: 10.1111/jan.14268
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of workplace violence and nurse outcomes: Gender difference study on a propensity score matched sample

Abstract: AimsTo investigate workplace violence and nurse outcomes by comparing gender differences.DesignA secondary analysis of cross‐sectional survey data.MethodsWorkplace violence was measured by four items from the International Hospital Outcome Study. Nurse outcomes were measured by tools including burnout, job satisfaction and intention to stay. We used propensity score matching to generate a sociodemographic balanced dataset of 108 male and 288 female nurses. A hypothetical relationship model was derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Other studies show a gender difference in the exposure of WPV, although research results are incongruent. For example, Acquadro Maran et al [24] report that female healthcare professionals were more often exposed to WPV perpetrated by patients' relatives than their male counterparts, while Li et al [25] found no significant gender differences. Edward et al [26] reported that male nurses were at higher risk to the exposure of physical violence while female nurses had a higher risk of verbal abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show a gender difference in the exposure of WPV, although research results are incongruent. For example, Acquadro Maran et al [24] report that female healthcare professionals were more often exposed to WPV perpetrated by patients' relatives than their male counterparts, while Li et al [25] found no significant gender differences. Edward et al [26] reported that male nurses were at higher risk to the exposure of physical violence while female nurses had a higher risk of verbal abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of physical WPV ranged from 4.9%–83.3% and verbal WPV from 66.2%–95.1% in the prior year among nurses (Jakobsson et al., 2020; Shi et al., 2020). Regards to association between gender and physical and verbal WPV, prior findings found are contradictory (Acquadro Maran et al., 2019; Li et al., 2020).…”
Section: Workplace Violence (Wpv) In Healthcare Systemsmentioning
confidence: 92%
“…Although violence occurs in all workplaces, nurses, with their close contact with the patient and their relatives, are three times more likely to be at risk of violence than other healthcare personnel. WPV can change the nurses’ attitude towards the profession of nursing and reduce their motivation, quality of care and career satisfaction (Boafo, 2018; Duan et al., 2019; Li et al., 2020; Liu et al, 2018; Tian et al., 2020).…”
Section: Workplace Violence (Wpv) In Healthcare Systemsmentioning
confidence: 99%
“…This global incidence identified in non‐mental health settings has led authors to propose that general hospital organisations prioritise workplace violence assessment and prevention measures, commensurate with mitigating its deleterious effects (Lamont & Brunero, 2018; Li et al, 2020; Pariona‐Cabrera et al, 2020; Zhang et al, 2020). Workplace violence has a significant impact on healthcare professionals safety and well‐being, both physically and psychologically (Lanctôt & Guay, 2014; Shi et al, 2017; Zafar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%